2020
DOI: 10.1097/md.0000000000020881
|View full text |Cite
|
Sign up to set email alerts
|

A risk stratification scoring system for new-onset atrial fibrillation after ischemic stroke

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…AF was diagnosed based on the ICD-9-CM code (427.31) in two consecutive outpatient visits or one hospital admission. The positive predictive value of AF diagnosis was around 90% in a previous validation study [ 22 ]. The definition of all-cause mortality and CV death were the same as those in the NHIRD registry data [ 16 , 23 ].…”
Section: Methodsmentioning
confidence: 98%
“…AF was diagnosed based on the ICD-9-CM code (427.31) in two consecutive outpatient visits or one hospital admission. The positive predictive value of AF diagnosis was around 90% in a previous validation study [ 22 ]. The definition of all-cause mortality and CV death were the same as those in the NHIRD registry data [ 16 , 23 ].…”
Section: Methodsmentioning
confidence: 98%
“…Their C-indices were below the accepted 0.7 threshold necessary to have clinical relevance at the individual patient level. Previous studies have shown that the C-indices of the CHADS 2 score ranged from 0.536 to 0.700 (12,18,19,22,36,37) and those of the CHA 2 DS 2 -VASc score varied between 0.578 and 0.706 (15,18,19,22,36,37), whereas the HATCH score attained C-indices of 0.612 and 0.653 (22). Only the C 2 HEST score achieved a C-index of 0.734 in the external validation cohort (15).…”
Section: Performance Of Risk Scores For Atrial Fibrillation Detected ...mentioning
confidence: 93%
“…Many studies have investigated prediction models for NDAF in the general population (25,42,43) or in selected patient groups such as those with stroke or TIA (18,21,22,31,44,45). Owing to the different characteristics of at-risk populations, it is arguable whether the relationships between the predictors and NDAF are similar across patient groups.…”
Section: Important Predictors Of Newly Detected Atrial Fibrillationmentioning
confidence: 99%